Cost-effectiveness of bedaquiline, pretomanid and linezolid for treatment of extensively drug-resistant tuberculosis in South Africa, Georgia and the Philippines - Francesca Conradie; Anna Vassall; Norbert Ndjeka; Gabriela Beatriz Gomez; Mariana Siapka; Anna Marie Celina Garfin; Nino Lomtadze; Zaza Avaliani; Nana Kiria; Shelly Malhotra; Sarah Cook-Scalise; Sandeep Juneja; et al. (BMJ Open)
Objectives Patients with highly resistant tuberculosis have few treatment options. Bedaquiline, pretomanid and linezolid regimen (BPaL) is a new regimen shown to have favourable outcomes after six months. We present an economic evaluation of introducing BPaL against the extensively drug-resistant tuberculosis (XDR-TB) standard of care in three epidemiological settings.Design Cost-effectiveness analysis using Markov cohort model.Setting South Africa, Georgia and the Philippines.Participants XDR-TB and multidrug-resistant tuberculosis (MDR-TB) failure and treatment intolerant patients.Interventions BPaL regimen.Primary and secondary outcome measures (1) Incremental cost per disability-adjusted life years averted by using BPaL against standard of care at the Global Drug Facility list price. (2) The potential maximum price at which the BPaL regimen could become cost neutral.Results BPaL for XDR-TB is likely to be cost saving in all study settings when pretomanid is priced at the Global Drug Facility list price. The magnitude of these savings depends on the prevalence of XDR-TB in the country and can amount, over 5 years, to approximately US$ 3 million in South Africa, US$ 200 000 and US$ 60 000 in Georgia and the Philippines, respectively. In South Africa, related future costs of antiretroviral treatment (ART) due to survival of more patients following treatment with BPaL reduced the magnitude of expected savings to approximately US$ 1 million. Overall, when BPaL is introduced to a wider population, including MDR-TB treatment failure and treatment intolerant, we observe increased savings and clinical benefits. The potential threshold price at which the probability of the introduction of BPaL becoming cost neutral begins to increase is higher in Georgia and the Philippines (US$ 3650 and US$ 3800, respectively) compared with South Africa (US$ 500) including ART costs.Conclusions Our results estimate that BPaL can be a cost-saving addition to the local TB programmes in varied programmatic settings.